Single Portal Technique for Subscapularis Tendon Repair - Elena, Nicholas (Arthrosc Tech, 2018)
The fast and steady development of arthroscopy techniques in the last couple of decades led to a drastic increase of arthroscopic rotator cuff repairs over the open procedure. Supraspinatus tears are the most common of all, but the subscapularis tendon tear is a more common injury than expected. Most of the time it presents as a partial tear or is associated with a subsequent rotator cuff tendon injury, especially the supraspinatus. Nowadays, the standard procedure to repair the subscapularis tendon is performed arthroscopically, even though a real superior result over the open repair it is yet to be reported. Ideally less operative time, less scarring, and postoperative pain would be the expected benefits, but no study has compared the long-term outcome of these 2 procedures yet. To maximize possible improvements, we would like to present an arthroscopic technique: a subscapularis tendon repair performed with the aid of an angled suture passer and using a single anterior working portal.